Risk factors of interventional radiology/surgery for colonic diverticular bleeding. Issue 3 (27th January 2021) - Sato, Yoshinori; Yasuda, Hiroshi; Nakamoto, Yusuke; Kiyokawa, Hirofumi; Yamashita, Masaki; Matsuo, Yasumasa; Maehata, Tadateru; Yamamoto, Hiroyuki; Mimura, Hidefumi; Itoh, Fumio
Abstract: Background and Aim: Colonic diverticular bleeding (CDB) stops spontaneously, but sometimes, excessive bleeding does not allow hemostasis and requires interventional radiology (IR)/surgery. We examined risk factors in patients who required IR/surgery for CDB and late recurrent bleeding rate after IR/surgery. Methods: This retrospective case–control study was conducted at a tertiary center. We included 608 patients who required hospitalization for CDB. Patients were investigated for risk factors using logistic regression analysis. We also investigated early and late recurrent bleeding rates following IR/surgery. Results: In 261 patients (42.9%), the bleeding source was identified, and endoscopic hemostasis was performed; 23 (3.8%) required IR/surgery. In multivariate analysis, shock state with a blood pressure of ≤90 mmHg ( P < 0.001; odds ratio [OR], 20.1; 95% confidence interval [CI], 5.08–79.5), positive extravasation on contrast‐enhanced computed tomography ( P < 0.001; OR 9.5, 95% CI 2.85–31.4), two or more early recurrent bleeding episodes ( P = 0.002; OR 7.4, 95% CI 2.14–25.4), and right colon as the source of bleeding ( P = 0.023; OR 4.1, 95% CI 1.25–14.0) were independent risk factors requiring IR/surgery. Early recurrent bleeding was observed in 0% and 28.0% patients ( P < 0.001) in the IR/surgery and no IR/surgery groups, respectively, whereas late recurrent bleeding rate was observed in 43.4% and 30.7% patients ( P = 0.203) in the IR/surgery and no IR/surgery groups, respectively. Four patients who required surgery experienced late recurrent bleeding at a site different from the initial CDB. Conclusions: Although IR/surgery is an effective hemostatic treatment wherein endoscopic treatment is unsuccessful, late recurrent bleeding cannot be prevented. Abstract : 23 (3.8%) colonic diverticular patietns required interventional radiology/surgery. We examined risk factors of interventional radiology/surgery of colonic diverticular bleeding. Although interventional radiology/surgery is an effective treatment, late recurrent bleeding cannot be prevented.